Hubungan antara prematuritas, berat badan lahir, jenis persalinan dan kelainan kongenital dengan kejadian asfiksia di RSI Fatimah - Johariyah Johariyah (Poltekkes Kemenkes Yogyakarta, 2017)
Major causes of neonatal mortality include 29% premature infants, sepsis and 25% pneumonia, and 23% are newborns withasphyxia and trauma. Birth asphyxia occupies the third leading cause of infant death in the world in the early period of life. Theincidence of asphyxia at provincial referral hospitals in Indonesia of asphyxia deaths was 41.94%. Research objective to determinethe relationship between prematurity, Low Birth Weight, type of labor and congenital abnormalities with asphyxia. The researchmethods is a case-control with retrospective approach will be compared the possible factors causing asphyxia. The first stage ofanalyze data is to perform descriptive of characteristic asphyxia based on prematurity, LBW, type of labor, and congenitalabnormalities. The second stage is to analyze the correlation between prematurity, LBW, type of labor and congenital abnormalitieswith asphyxia by Chi-Square. The results showed that most of the asphyxia occurrence occurred in infants with mature age (59.2%),spontaneous labor (53.0%), normal birth weight (71.4%) and no abnormalities congenital (99%). Based on the result of analysisfound that there is a significant relationship between prematurity, type of labor, LBW with asphyxia and no relationship betweencongenital aberration with asphyxia occurrence.